Optimizing Cluster Head Selection through improved Memetic Algorithm and Blockchain Technology for Securing WSN - Huda H. Ali; Ruwaida M. Yas; Maysaa H. Abdulameer (Eximia, 2024)
Wireless Sensor Networks (WSNs) contain numerous wireless sensor nodes positioned around the geographical positions. The WSN used in several applications necessity to be efficient and secured, Hence the organization of trustworthy nodes and links in WSN offers more secure data transmission in Secured Wireless Sensor Networks (SWSNs) , Therefore, construction of secure and efficient WSN is acritical and challenged task. In this paper, for efficiently choose of cluster head (which is work to have data from the S.Ns and deliver it to the B.S) Improved Memetic Algorithms is proposed to used. Moreover, to ensure cluster head (CH) authenticity in order to identify malicious nodes and avoid attacks, Blockchain technique is implemented, in the proposed method; mischievous nodes would be found and removed from the WSN. Finally choosing the best route based on two parameters, residual energy and the distance from next CH and Basie station (BS). The proposed methodology proved its efficiency and security through simulation implementation results, which compared with similar study results.